2013
DOI: 10.4049/jimmunol.1301262
|View full text |Cite
|
Sign up to set email alerts
|

TLR1/2 Ligand–Stimulated Mouse Liver Endothelial Cells Secrete IL-12 and Trigger CD8+ T Cell Immunity In Vitro

Abstract: Liver sinusoidal endothelial cells (LSECs) are unique organ-resident APCs capable of Ag cross-presentation and subsequent tolerization of naive CD8+ T cells. Under certain conditions, LSECs can switch from a tolerogenic to an immunogenic state and promote the development of T cell immunity. However, little is known about the mechanisms of LSECs to induce T cell immunity. In this study, we investigated whether functional maturation of LSECs can be achieved by TLR ligand stimulation and elucidated the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 41 publications
3
72
0
Order By: Relevance
“…An appropriate T cell response is required to eradicate HBV and HCV, while exhausted HCV-specific T cells with inhibitory immune receptors, such as PD-1 and CTLA-4, account for persistent viral infection within the liver (3, 4, 81, 82). LSECs with up-regulated PD-L1 expression were reported to induce antigen-specific T cell tolerance (40), and recent reports indicated that stimulation of LSECs with TLR1/2 ligands, but not TLR3 or TLR4 ligands could overcome liver-specific tolerance (83). Further study is required to clarify the effect of TLR1/2 ligands on the function of tolerant HBV- and HCV-specific T cells.…”
Section: Role Of Tlrs In Murine and Human Liver Injurymentioning
confidence: 99%
“…An appropriate T cell response is required to eradicate HBV and HCV, while exhausted HCV-specific T cells with inhibitory immune receptors, such as PD-1 and CTLA-4, account for persistent viral infection within the liver (3, 4, 81, 82). LSECs with up-regulated PD-L1 expression were reported to induce antigen-specific T cell tolerance (40), and recent reports indicated that stimulation of LSECs with TLR1/2 ligands, but not TLR3 or TLR4 ligands could overcome liver-specific tolerance (83). Further study is required to clarify the effect of TLR1/2 ligands on the function of tolerant HBV- and HCV-specific T cells.…”
Section: Role Of Tlrs In Murine and Human Liver Injurymentioning
confidence: 99%
“…59 Recently, we examined functional maturation of LSECs by TLR ligand stimulation, demonstrating that pretreatment of LSECs with P3C (TLR1/2 ligand) but not poly(I:C) (TLR3 ligand) or LPS (TLR4 ligand) reverted their suppressive properties to induce specific T-cell immunity. 60 IL-12, which was produced at a low but sustainable level after TLR2 stimulation, was identified as one essential mediator for LSEC-mediated CD8 1 Tcell immunity. 60 In chronically HBV-infected patients, it was demonstrated that IL-12 but not IFN-a is capable of rescuing the anti-viral function of exhausted HBV-specific CD8 1 T cells.…”
Section: Activation Of Tlr-mediated Signaling Pathways Modulates Hbv-mentioning
confidence: 99%
“…60 IL-12, which was produced at a low but sustainable level after TLR2 stimulation, was identified as one essential mediator for LSEC-mediated CD8 1 Tcell immunity. 60 In chronically HBV-infected patients, it was demonstrated that IL-12 but not IFN-a is capable of rescuing the anti-viral function of exhausted HBV-specific CD8 1 T cells. 61 Therefore, we speculate that activation of the TLRmediated signaling pathway may lead to an enhancement of HBV-specific T-or B-cell responses in the liver.…”
Section: Activation Of Tlr-mediated Signaling Pathways Modulates Hbv-mentioning
confidence: 99%
“…Prior work in LSECs has largely focused on Toll-like receptor (TLR)-4 and its ligand, lipopolysaccaride (LPS), which is constantly present in the portal venous blood 67 . However, the precise role of LSECs in sensing other TLR ligands, such as viral products, is just beginning to emerge 6, 8, 9 . Moreover, in addition to the TLR system, retinoic acid inducible gene-I (RIG-I)-like receptors (RLRs) have been identified as cytosolic receptors for intracellular double-stranded RNA sensing 10 .…”
Section: Introductionmentioning
confidence: 99%